A CEFR-Oriented Probe into Culture: Implications for Language Learners - Ibrahim Halil Topal (CV. Rustam, 2024)
The Common European Framework for Languages (CEFR), adopted by the Council of Europe (2001), is an action-based framework for language education, teaching and assessment in Europe. CEFR's descriptions of language skills across all skill levels can guide language learners, educators, and assessors. Alongside language-related issues, one phenomenon considered highly by the CEFR is culture – a concept intricately connected with language. Given the significance of culture and related concepts for language education, this study evaluated the CEFR and Companion Volume to draw inferences about culture and explore the possible implications for language learners. To this end, the two volumes were subjected to content analysis. Findings indicated several types of cultural awareness (n=7), knowledge (n=4), competence (n=8), and strategy (n=1) that language learners must adopt for successful cross-cultural interactions. These cultural expectations might also be considered under plurilinguistic awareness, knowledge, competence, and strategies. The study is expected to contribute theoretically and practically since it intends to bridge the literature gap. Prospective research, however, is urged to corroborate the findings. Furthermore, the study is expected to guide future studies tackling the significance of culture for language learners within the CEFR.